Sharia Financing Online Education: Mudhorobah, Musyarokah and Murobahah Financing - Achmad Maulana; Nena Alfiana; Fitriani Syahrir; Sabrina Fitri Ferilli Khoirunisa (Journal of Islamic Economy and Community Engagement, 2023)
The development of digital technology has benefits as a learning support material. Instagram is a social media network that can be used to share photos or videos. This service aims to utilize Instagram social media for the purposes of Syairah investment education: Sukuk. The results of this activity show quite satisfactory results with 781 views and 69 likes and several comments that show the enthusiasm of Instagram users for the Sukuk Sharia investment education video. In the future, it is hoped that activities like this can be reproduced not only through Instagram but also through other social media.